Autoestudo relacionado à justiça social nas aulas de educação física: explorando a técnica de incidentes críticos - Silva, Jorlany Pereira da (2024)
This dissertation is anchored in a self-study in which I seek to analyze my own pedagogical actions from the perspective of a pedagogy intentionally directed towards the promotion of social justice. My research problem is the occurrence and invisibility of social injustice situations in my physical education classes. Amid this self-study, my specific objectives are: to evaluate the implications of an authorial learning path and the technique of critical incidents as strategies to foster critical and reflective dialogues about social justice; to verify how my own experiences, values, and positions influence my perception and approach to situations of social injustice in my classes; and to identify the main challenges and opportunities associated with adopting a pedagogy intentionally directed towards promoting social justice in my pedagogical practice. In the theoretical framework, I explored the central themes of my research, highlighting the importance of the critical incidents technique as a strategy to identify and understand situations of social injustice in physical education classes; I delved into the discussion on social justice, addressing its different dimensions and challenges in the educational context; And finally, I contextualized self-study and critical friendship as a reflective and critical approach. The research was conducted with 39 students from the 2nd year of the technical course in computer science at the Instituto Estadual de Educação, Ciência e Tecnologia do Maranhão – IEMA, in the city of Chapadinha – MA, and had the collaborative support of a critical friend, a physical education teacher and self-study teacher-researcher. The research adopted a qualitative approach, centered on the use of the critical incidents technique and having self-study as the main methodology. Data collection was carried out through a field diary, focus groups, and a critical incidents observation instrument adapted from Philpot et al. (2021). Data analysis was conducted through the triangulation of empirical data collected to identify the prominent themes, and then the results were presented through thematic analysis. The obtained results indicated that the development of a self-critical awareness and the promotion of a pedagogical practice aligned with the principles of social justice are fundamental elements to address and confront situations of social injustice in physical education classes, and emphasized the relevance of a dialogical, reflective, and critical approach for the integral and emancipatory development of the students.